Glosa do wyroku Naczelnego Sądu Administracyjnego z 31 stycznia 2023 r., sygn. akt III OSK 1008/22 (dokonywanie zakupów na zasadach powszechnej dostępności a wygaśnięcie mandatu radnego gminnego) - Trela, Anna (Studia Prawa Publicznego, 2023)
The gloss deals with an analysis of the provision of Art. 24f sec. 1 of the Act of 8 March 1990 on commune self-government (u.s.g.), from which it follows that councillors may not conduct business activity on their own account or jointly with other persons using the communal property of the municipality in which the councilor obtained the mandate, as well as managing such activity or be the representative or proxy in the conduct of such activities. Violation of this prohibition results in the loss of the ticket. The established anticorruption provision still raises many doubts. As a rule, it is assumed that due to its purpose and the subject and scope of violations, this prohibition is not absolute. Particularly controversial is the use of municipal property by the councillor on the principles of its universal availability, consisting in making purchases in the councillor’s shop, which do not require the use of public procurement. In order to clarify the essence of this case, the issues that do not raise doubts under Art. 24f sec. 1 u.s.g. and which entail the absolute necessity of terminating the mandate of the councillor are discussed ﬁrst. Following this, judgments are presented in which administrative courts found that the use of property on the basis of general availability is allowed unless it privileges the position of the councillor and any purchases made in stores owned by the councillor do not result from prior arrangements or contracts. The development of this concept is dictated by the content of constitutional provisions and the ratio legis of Art. 24f sec. 1 u.s.g.